Economic aspects of recently introduced trypanotolerant livestock production under trypanosomiasis risk in southern Togo - Morkramer, G.; Defly, A.; D'Ieteren, G.D.M.; Grundler, G.; Itty, P.; Leak, S.G.A.; Maehl, J.H.H.; Mawuena, K.; Nagda, S.M.; Rarieya, J.M.; Thorpe, W.R.; Trail, J.C.M. (ILCA/ILRAD, 1988)
Report of a study on the economics of trypanotolerant livestock production with station cattle and village cattle and sheep. Presents data on overall cattle & sheep production parameteres, economic parameters including veterinary services, veterinary treatments, fodder, mineral blocks, night kraul and herdomen. Gives the distribution & annual overall cost of production inputs per animal.